2017
DOI: 10.1002/solr.201700030
|View full text |Cite
|
Sign up to set email alerts
|

Approaching Solar‐Grade a‐Si:H for Photovoltaic Applications via Atmospheric Pressure CVD Using a Trisilane‐Derived Liquid Precursor

Abstract: The article demonstrates the fabrication of a-Si:H thin films in a N 2 -filled glove box via atmospheric pressure chemical vapor deposition (APCVD) using a vaporized silicon hydride polymer/silicon nanoparticle composite ink prepared from trisilane (Si 3 H 8 ). It is shown via Raman spectroscopy that the films exhibit good short and mid-range atomic order. Fourier transform infrared spectroscopy reveals a fairly compact microstructure and a hydrogen concentration of 13-18 at.%. Photothermal deflection spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…Such a shift implies the formation of the interaction between C 60 (main body of PCBM) and ClGD . Moreover, in comparison with unbonded ClGD, the vibration of acetylenic linkages (—C—C≡C—C—) of ClGD‐PCBM at around 2191.9 cm −1 was weakened, which may be attributed to the decline of the energy of the corresponding phonon modes due to the existence of π–π interaction between ClGD and PCBM . X‐ray photoelectron spectroscopy (XPS) was performed to further investigate the interaction between ClGD and PCBM.…”
Section: Resultsmentioning
confidence: 99%
“…Such a shift implies the formation of the interaction between C 60 (main body of PCBM) and ClGD . Moreover, in comparison with unbonded ClGD, the vibration of acetylenic linkages (—C—C≡C—C—) of ClGD‐PCBM at around 2191.9 cm −1 was weakened, which may be attributed to the decline of the energy of the corresponding phonon modes due to the existence of π–π interaction between ClGD and PCBM . X‐ray photoelectron spectroscopy (XPS) was performed to further investigate the interaction between ClGD and PCBM.…”
Section: Resultsmentioning
confidence: 99%
“…Figure (j,k) presents the Raman spectra of GD and GDZO, and it is observed that the Ag(2) pentagonal pinch mode of the GDZO shifted from 1399.2 cm −1 (pristine GD) to 1364.7 cm −1 (GDZO), and 1594.2 cm −1 (pristine GD) to 1583.1 cm −1 (GDZO), respectively. The redshifts of GDZO imply that the adduct between GD and ZnO is formed, and thus the energy of the corresponding phonon modes is declined and the bond of CC and CC is weakened, which explains that the vibration of acetylenic linkages (CCCC) at around 2183.3 cm −1 become weakened compared with the signal of the unbonded GD …”
Section: Resultsmentioning
confidence: 99%
“…300 °C) in comparison to the ca. 550 °C needed to deposit silicon from SiH 4 . Poly­(dihydrosilane) [SiH 2 ] n has been postulated to be an intermediate in the thermal or photoinitiated ring-opening polymerization (ROP) of cyclo -Si 6 H 12 , a process that eventually yields hydrogenated amorphous bulk silicon (a-SiH) . The formation of [SiH 2 ] n as an orange solid has been documented in the 1980s from the Wurtz-type reductive coupling of H 2 SiCl 2 with Li metal, while treatment of calcium silicide (CaSi) with HCl is reported to give a brown solid with the estimated composition SiH 0.9 .…”
Section: Molecular Hydrides Of the Group 14 Metals (Silicon Germanium...mentioning
confidence: 99%